2017
DOI: 10.1002/jssc.201700484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and quantitative analysis of 11 compounds in Morinda officinalis using ultra‐high performance liquid chromatography and photodiode array detection coupled with chemometrics

Abstract: Morinda officinalis (Rubiaceae) is a traditional Chinese medicine widely used for the treatment of impotence and osteoporosis in clinical therapy. In the present study, a rapid and simple ultra-high performance liquid chromatography with photodiode array detection method was developed and validated for the simultaneous determination of 11 bioactive compounds in M. officinalis. This assay method was validated with respect to linearity (R > 0.9991), precision, repeatability, limit of detection, limit of quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Various chromatographic methods have been developed for the quantitative analysis and characterization of TCMs. Among them, some methods, including high-performance liquid chromatography (HPLC)–ultraviolet (UV) [8,9,10,11] and liquid chromatography (LC)–tandem mass spectrometry (MS/MS) [12,13] have been applied in the detection of active ingredients in TCMs. However, since some natural product compounds lack the chromophores required for UV detection, they cannot be directly detected using UV.…”
Section: Introductionmentioning
confidence: 99%
“…Various chromatographic methods have been developed for the quantitative analysis and characterization of TCMs. Among them, some methods, including high-performance liquid chromatography (HPLC)–ultraviolet (UV) [8,9,10,11] and liquid chromatography (LC)–tandem mass spectrometry (MS/MS) [12,13] have been applied in the detection of active ingredients in TCMs. However, since some natural product compounds lack the chromophores required for UV detection, they cannot be directly detected using UV.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several analytical methods based on HPLC coupled to ultraviolet detection (UV) [ 13 , 14 , 15 , 16 , 17 ] or mass spectrometry (MS) (Li et al, 2016) have been reported for the determination of anthraquinones or iridoid glycosides in M. officinalis . However, these methods suffered from low resolution or long run-time, with few of these investigations being conducted for the simultaneous determination of multicomponents in this herbal medicine [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly eliminates the overlap and correlation in the chemical information through the dimensionality reduction of the data, and the multidimensional index becomes a simple index under the premise of losing little information, so that the data are simpler, more intuitive, and clearer [26]. PCA is widely used to evaluate the differences between the quality of Chinese herbal medicines and processed products [27]. The content of raw and processed FF was calculated in three dimensions.…”
Section: Resultsmentioning
confidence: 99%